The Effect of Profitability, Company Size and Liquidity on Stock Prices with Dividend Policy as a Moderating Variable (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange in 2023) - Jihan Dwi Handayani; Aty Herawati (Dinasti International Journal of Digital Business Management, 2024)
There is a trend of decreasing stock price data in the period 2022-2023 in the Banking sub-sector, and there are differences in the results of previous studies related to the variables used. In this study, the Moderation Regression Analysis Method is used to test the role of moderating variables in influencing the relationship between the independent variables and the dependent variable. The purpose of this study is to test the effect of Profitability (Return on Assets), Company Size (Total Assets), and Liquidity (Loan to Deposit Ratio) on the stock prices of banking companies listed on the Indonesia Stock Exchange in 2023 by choosing dividend policy (Dividend Payout Ratio) as a moderating variable. The population selected in this study were banking companies listed on the IDX, then determined to be 17 sample companies that could be continued for the research process. After conducting the study, the results showed that Profitability (Return on Assets), Company Size (Total Assets), Liquidity (Loan to Deposit Ratio) had a positive and significant effect on the company's Stock Price, both directly and when moderated by dividend policy.